Biased clustered substitutions in the human genome: The footprints of male-driven biased gene conversion - Dreszer, Timothy R.; Wall, Gregory D.; Haussler, David; Pollard, Katherine S.

(untitled) (Genome Research, 2007)
We examined fixed substitutions in the human lineage since divergence from the common ancestor with the chimpanzee, and determined what fraction are AT to GC (weak-to-strong). Substitutions that are densely clustered on the chromosomes show a remarkable excess of weak-to-strong “biased” substitutions. These unexpected biased clustered substitutions (UBCS) are common near the telomeres of all autosomes but not the sex chromosomes. Regions of extreme bias are enriched for genes. Human and chimp orthologous regions show a striking similarity in the shape and magnitude of their respective UBCS maps, suggesting a relatively stable force leads to clustered bias. The strong and stable signal near telomeres may have participated in the evolution of isochores. One exception to the UBCS pattern found in all autosomes is chromosome 2, which shows a UBCS peak midchromosome, mapping to the fusion site of two ancestral chromosomes. This provides evidence that the fusion occurred as recently as 740,000 years ago and no more than ∼3 million years ago. No biased clustering was found in SNPs, suggesting that clusters of biased substitutions are selected from mutations. UBCS is strongly correlated with male (and not female) recombination rates, which explains the lack of UBCS signal on chromosome X. These observations support the hypothesis that biased gene conversion (BGC), specifically in the male germline, played a significant role in the evolution of the human genome.